The Effect of Addition Liquid Organic Supplement from Rabbit Feces on the Chemical Properties and Fleigh Value of Fermented Rice Bran - Audhya, Shella; Hernaman, Iman; Ayuningsih, Budi; Rosani, Urip (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
Fermentation of rice bran is a way to increase the nutrient content and palatability of livestock when consuming it. The study was conducted at the Ruminant Animal Nutrition Laboratory, Faculty of Animal Husbandry, Padjadjaran University in Jatinangor, Sumedang. This study aims to determine the effect of using Liquid Organic Supplement (LOS) of rabbit feces in making fermented rice bran on pH, dry matter loss, lactic acid content, and Fleigh value (NF). The study was conducted experimentally using a Completely Randomized Design (CRD). There were three treatments, namely P0 (1 kg of rice bran: 300 g molasses), P1 (1 kg of rice bran: 200 g molasses: 100 g SOC of rabbit feces), and P2 (1 kg of rice bran: 100 g molasses: 200 g SOC of rabbit feces). The research data were processed using analysis of variance and Duncan's distance test. The results showed that the treatment increased the lactic acid content, but decreased the pH, dry matter loss, and Fleigh value. Treatment P2 produced fermented rice bran with the highest lactic acid content (45,8%), the lowest pH (3,99), dry matter loss (1,31%), and the highest Fleigh value (199). The conclusion of this study is that the ratio of rice bran, molasses, and SOC of 10:1:2 can produce the best fermented rice bran.